Effectiveness of a Behavioral Intervention vs. Standard Care for Pediatric Obesity: A Randomized Controlled Trial - Oneeb, Afshin; Olayiwola, Aminat; Pahlajrai, Nirmaldas; Ihsan Ullah; Khan, Sheheryar Alam (Indus Journal of Bioscience Research, 2025)
Background: Pediatric obesity is a growing public health issue, leading to long-term health risks such as diabetes, cardiovascular disease, and psychological distress. Standard care approaches, which primarily focus on general lifestyle advice, often show limited success. This study examines whether a structured behavioral intervention is more effective than standard care in managing childhood obesity. Methods: This randomized controlled trial was conducted at Jinnah Teaching Hospital from September 1, 2024, to February 28, 2025. A total of 110 children aged 6 to 14 years with obesity were randomly assigned to either a behavioral intervention group (n=55) or a standard care group (n=55). The intervention group participated in a structured program involving dietary education, physical activity sessions, and behavioral counseling, while the standard care group received general weight management advice. Primary outcomes included changes in BMI, body fat percentage, and waist circumference. Secondary outcomes assessed metabolic markers, dietary habits, physical activity levels, and psychological well-being. Data were analyzed using SPSS, with a p-value of <0.05 considered statistically significant. Results: Children in the behavioral intervention group showed a significant reduction in BMI (–1.7 kg/m², p<0.01), body fat percentage (–3.6%, p<0.01), and waist circumference (–4.6 cm, p<0.01) compared to the standard care group. Metabolic improvements were also observed, including lower fasting glucose and insulin resistance scores. Additionally, participants in the intervention group reported increased physical activity, improved dietary habits, and higher psychological well-being scores. Conclusion: A structured behavioral intervention was more effective than standard care in reducing obesity-related health risks in children. The findings support the integration of multidisciplinary behavioral programs into routine clinical practice to improve pediatric weight management outcomes.